CONDITIONS AFFECTING IMPORTS OF MUNG BEANS IN INDONESIA - Hazhiyah Azzahara; Elpawati Elpawati; Armaeni Dwi Humaerah (Syarif Hidayatullah State Islamic University Jakarta, 2025)
Mung beans are believed to be the key to Indonesia's food security in facing the food crisis in the future. This study aims to analyze the factors that influence the volume of mung bean imports in Indonesia. The factors studied include domestic production, import prices, exchange rates, domestic prices, and government policies. The data used are secondary data from 2007 to 2022, obtained from Statistics Indonesia (BPS), the Ministry of Agriculture, and UN Comtrade. Multiple linear regression was used to determine the effect of each independent variable on the volume of mung bean imports. Based on the EViews regression output, three variables were found to have a significant effect on the volume of mung bean imports in Indonesia: domestic production (negative effect), real domestic prices (positive effect), and import policy (significant effect). Meanwhile, real import prices and the exchange rate of the Rupiah against the US Dollar showed negative but statistically insignificant effects. These findings indicate that fluctuations in mung bean imports in Indonesia are more strongly influenced by domestic production levels, internal price dynamics, and government policies rather than external factors such as import prices and currency exchange rates.